Trabectedin-Related Heart Failure: Case Report and a Systematic Review of the Literature - Catherine, Julien; Jungels, Christiane; Durieux, Valerie; Deliens, Coralie; Grigoriu, Bogdan (Frontiers in Oncology, 2021)
New drugs come not only with benefits but also with unexpected toxicities which need to be promptly recognized and managed. Starting from a scholar case of acute heart failure with preserved ejection fraction following the administration of trabectedin (ET-743, Yondelis®) in a patient with a metastatic solitary fibrous tumor, we performed a systematic review of the literature encompassing the results of previous cardiac safety analysis published ten years ago, a review of clinical trials published during the last 10 years as well as single-case descriptions related to trabectedin cardiotoxicity. The estimated incidence of cardiac toxicity was 3,4% among patients receiving trabectedin, with recent data suggesting a higher rate of heart failure than previously recognized. Previous or concomitant anthracyclines exposure may represent a risk factor. Assaying for NT-pro-BNP may be useful for the early detection of individuals with trabectedin-induced heart failure.